Preparation method of nano metal oxide Ni3V2O8 doped with aluminum hydride composite hydrogen supply material
By doping nanometal oxide Ni3V2O8 catalyst in aluminum hydride, the problems of high hydrogen release temperature and poor kinetic performance of aluminum hydride are solved, and the efficient hydrogen release performance of aluminum hydride is achieved, which is suitable for applications in areas such as portable fuel cells and drones.
Patent Information
- Application Number
- CN202411247127.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-09-06
AI Technical Summary
As a solid hydrogen storage material, aluminum hydride has the problems of high hydrogen release temperature and poor kinetic performance, which limits its large-scale application in the fields of portable fuel cells and drones.
By doping the nanometal oxide Ni3V2O8 catalyst in aluminum hydride, the interaction between Ni and V transition metals is used to create a polyvalent chemical environment in situ to improve the hydrogen release performance of aluminum hydride. The catalyst is prepared by solid phase sintering method and solvent thermal method, and is mixed with aluminum hydride by mechanical ball milling method.
The initial hydrogen discharge temperature of aluminum hydride is significantly reduced to 72-75°C, and the hydrogen discharge amount and kinetic performance are improved. It is suitable for applications in the fields of portable fuel cells and drones.
Smart Images

Figure CN119118058B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum hydride hydrogen storage, and specifically relates to a method for preparing a nano metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material. Background Art
[0002] Hydrogen energy is a secondary energy source with high energy density (142MJ / kg), clean zero carbon emissions, abundant sources, wide application range and various forms of utilization. It is considered to be an ideal energy storage method for achieving the low-carbon transformation of the energy system in the new era. However, the actual application of hydrogen energy is limited by the technical bottlenecks of its storage and transportation. Therefore, in order to achieve the widespread application of hydrogen energy, the development of safe and efficient hydrogen storage and transportation technology is a top priority. Solid-state hydrogen storage has the advantages of high energy density, good safety performance, easy storage and transportation, and is currently the most promising hydrogen storage method.
[0003] Among many solid hydrogen storage materials, aluminum hydride (AlH3) has excellent mass hydrogen storage density (10.1wt%) and relatively mild hydrogen desorption temperature (150-200℃). It is one of the current research hotspots in the field of solid hydrogen storage and is a relatively ideal hydrogen source for portable batteries. It is expected to be used in military power supplies, military and civilian dual-use drones and other fields. However, as a hydrogen source for portable fuel cells, it has relatively high hydrogen desorption temperature and poor kinetic performance, which greatly hinders the large-scale application of AlH3. Among the many methods to improve the hydrogen desorption performance of AlH3, adding catalysts is a simple and effective modification method. Currently, the commonly used catalysts mainly include transition metal fluorides, oxides and rare earth metal oxides, which can effectively reduce the hydrogen desorption temperature of AlH3 and improve the hydrogen desorption kinetic performance, but there is still a problem of high hydrogen desorption termination temperature, which is not conducive to the practical application of portable fuel cell hydrogen supply systems (operating temperature 60-120℃).
[0004] Most transition metals have variable valence states due to the existence of unfilled valence d orbitals. Based on this characteristic, transition metal-based catalysts, such as vanadium-based catalysts, will produce intermediate valence active catalytic substances during the mechanical ball milling process with aluminum hydride, thereby improving the dehydrogenation performance of aluminum hydride, reducing its dehydrogenation operating temperature and dehydrogenation reaction kinetics, thereby promoting its industrial application in the fields of drones, vehicle-mounted fuel cells, etc.
[0005] Based on this, the present invention is proposed. Summary of the invention
[0006] In view of the above technical problems, the present invention aims to provide a method for preparing a nano metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material, wherein a V2AlC precursor is prepared by a solid phase sintering method, and then a Ni3V2O8 catalyst is prepared by a solvent thermal method. The catalyst is ball-milled with aluminum hydride to prepare the composite hydrogen supply material. The present invention utilizes the interaction between Ni and V transition metals to create a multivalent chemical environment in situ to improve the hydrogen release performance of aluminum hydride, showing an excellent catalytic effect. The preparation process is simple and controllable, and is easy to promote and apply in industry.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a nano-metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material is carried out in the following steps in sequence:
[0009] S1. Preparation of precursor V2AlC
[0010] V powder, Al powder and graphite powder were uniformly mixed in a molar ratio of 2:1.3:1, and V2AlC powder was prepared by a solid phase sintering method;
[0011] S2. Preparation of Nano-Metal Oxide Catalyst Ni3V2O8
[0012] Nickel nitrate hexahydrate was dissolved in 10% acetic acid solution, and then V2AlC powder was added, and after ultrasonic dispersion, it was transferred to a hydrothermal reactor and placed in a 200°C forced air drying oven for solvothermal reaction. The product after the reaction was centrifugally washed and dried, and the product was collected to obtain a nano-metal oxide catalyst Ni3V2O8;
[0013] The hydrothermal process is the key process for forming the durian shell-like cone-shaped structure of Ni3V2O8. In this process, the hydrothermal reaction time, temperature, raw material ratio, etc. affect the composition and morphology of the product. When the hydrothermal reaction temperature is too low, the reaction is incomplete and impurities are present. When the hydrothermal reaction time is short, the raw materials are not completely reacted, a block structure exists, and a flaky structure is easily formed. When the reaction time is too long, the structure of the product will be destroyed, and growth and agglomeration will occur. When the raw material ratio is too high or too low, the reaction is prone to incomplete.
[0014] S3. Preparation of nano-metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material
[0015] Aluminum hydride and nano-metal oxide catalyst Ni3V2O8 were mixed and a composite hydrogen supply material was prepared by mechanical ball milling in an argon atmosphere.
[0016] As a limitation of the present invention, in step S1, the molar ratio of V powder, Al powder and graphite powder is 2:1.3:1, and the solid phase sintering method uses argon as the sintering atmosphere, firstly increases the temperature to 600°C at a heating rate of 5°C / min, and then increases the temperature to 1500°C at a heating rate of 10°C / min. The reaction temperature is 1500°C and the reaction time is 300min.
[0017] As a second limitation of the present invention, in step S2, the mass ratio of nickel nitrate hexahydrate to V2AlC powder is 93:15, and the size of the V2AlC is 600 mesh.
[0018] The ratio of nickel nitrate hexahydrate to V2AlC powder of the present invention is the key to forming a durian shell-like conical structure Ni3V2O8. When the ratio of the two is too large or too small, a durian shell-like conical structure Ni3V2O8 with uniform size and morphology cannot be formed.
[0019] As a third limitation of the present invention, in step S2, the hydrothermal reaction time is 30 hours.
[0020] The hydrothermal reaction time of the present invention is also the key factor affecting the morphology of Ni3V2O8. When the hydrothermal reaction time is too long or too short, a durian shell-like conical structure Ni3V2O8 with relatively uniform size and morphology cannot be formed.
[0021] As a fourth limitation of the present invention, in step S2, the centrifugal washing is to wash the product with deionized water and anhydrous ethanol respectively for 4 to 6 times, each time centrifugation for 3 minutes.
[0022] As a fifth limitation of the present invention, in step S2, the drying temperature is 60° C. and the drying time is 24 hours.
[0023] As a sixth limitation of the present invention, in step S3, the doping amount of the nano metal oxide catalyst Ni3V2O8 is 5wt%.
[0024] As the seventh limitation of the present invention, in step S3, the ball-to-material ratio of the mechanical ball milling is 60:1, the ball milling speed is 350 r / min, the ball milling time is 1 h, and the volume of the ball milling jar is 250 mL.
[0025] Ball milling is the process of forming the final composite hydrogen-desorbing material. During the ball milling process, Ni3V2O8 interacts with AlH3, causing the +2-valent Ni and +5-valent V in Ni3V2O8 to transform into Ni 2+ 、Ni 0 and V 4+ 、V 0 As catalytically active substances, they synergistically catalyze and improve the hydrogen desorption performance of AlH3.
[0026] The present invention has another limitation, that the nano metal oxide catalyst Ni3V2O8 is a conical structure similar to the shell of a durian.
[0027] As is known to all, the morphology and structure of the product have a great influence on its performance. The catalyst Ni3V2O8 of the present invention has a conical structure similar to the shell of a durian. This structure can help to reduce the size of AlH3 particles, thereby improving the hydrogen decomposition performance of AlH3, reducing the hydrogen decomposition temperature, and improving the hydrogen decomposition kinetics.
[0028] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, which jointly determine the morphological characteristics and performance of the product.
[0029] The above technical solution has the following advantages or beneficial effects:
[0030] 1. The preparation method of the present invention is simple, the process is easy to control, the cycle is short, and it is easy to industrialize production and promote application.
[0031] 2. The catalyst Ni3V2O8 prepared by the present invention has excellent catalytic activity.
[0032] 3. The initial dehydrogenation temperature of the nano-metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material prepared by the present invention is reduced to 72-75°C, and the dehydrogenation amount is as high as 8.2wt%; the dehydrogenation amount in 20 minutes at 100°C is as high as 6.3wt%, which has excellent dehydrogenation performance.
[0033] The invention is suitable for preparing nano metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 X-ray diffraction patterns of V2AlC and Ni3V2O8-30h prepared in Example 1 of the present invention;
[0035] Figure 2 The SEM and EDS images of Ni3V2O8-30h prepared in Example 1;
[0036] Figure 3 XPS spectra of Ni 2p, V 2p and O1s of Ni3V2O8-30h prepared in Example 1;
[0037] Figure 4 This is the hydrogen desorption performance diagram of AlH3-5wt%Ni3V2O8-30h and AlH3-5wt%V2AlC in Examples 1 and 2. DETAILED DESCRIPTION
[0038] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0039] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0040] Example 1 Preparation method of a nano-metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material
[0041] S1. Preparation of precursor V2AlC
[0042] V powder, Al powder and graphite powder were mixed uniformly in a molar ratio of 2:1.3:1, and in a high-temperature tube furnace, argon was used as a protective atmosphere, the temperature was increased to 600°C at a rate of 5°C / min, and then increased to 1500°C at a rate of 10°C / min, and kept at 1500°C for 300 minutes, and solid-phase sintering was performed to prepare a V2AlC precursor, and the obtained V2AlC block solid was crushed, ground and passed through a 600-mesh sieve for subsequent experiments to obtain V2AlC powder;
[0043] S2. Preparation of Nano-Metal Oxide Catalyst Ni3V2O8
[0044] 0.93g of nickel nitrate hexahydrate was added to 15mL of 10% acetic acid solution, and stirred at 500rpm for 30min at room temperature to form a uniform solution A; 0.15g of V2AlC powder was added to solution A, and ultrasonicated at 500W for 30min to form a mixed solution B; the mixed solution B was transferred to a 25mL polytetrafluoroethylene reactor, sealed and placed in a blast drying oven at 200°C for 30h; after the reaction was completed and cooled to room temperature, it was centrifuged and washed with deionized water and anhydrous ethanol at a speed of 8000rpm and a single centrifugation time of 3min, first centrifuged with deionized water for 4 to 6 times, and then centrifuged with anhydrous ethanol for 2 to 3 times; finally, the obtained precipitate was placed in a 60°C vacuum drying oven and dried for 24h to obtain a nano metal oxide catalyst Ni3V2O8, which was recorded as Ni3V2O8-30h;
[0045] S3. Preparation of Nano-metal Oxide Ni3V2O8 Doped Aluminum Hydride Composite Hydrogen Supply Material
[0046] Using argon as the protective atmosphere and a ball-to-material ratio of 60:1, 950 mg of aluminum hydride and 50 mg of Ni3V2O8 (catalyst doping amount is 5 wt%) were ball-milled at a speed of 350 r / min for 1 h to prepare a composite hydrogen supply material, recorded as AlH3-5wt%Ni3V2O8-30h.
[0047] The nano-metal oxide catalyst Ni3V2O8 prepared in this example was characterized and measured. Figure 1 The XRD test proved that the characteristic peak of V2AlC disappeared after the reaction, and the characteristic peak of Ni3V2O8 appeared, indicating that Ni3V2O8 was successfully synthesized.
[0048] In order to prove the structural characteristics of the prepared nano-metal oxide catalyst Ni3V2O8, SEM and EDS characterization were performed. Figure 2 As shown, Ni3V2O8-30h presents a conical structure similar to the shell of a durian; EDS results show that Ni, V and O elements are evenly distributed.
[0049] In order to prove the chemical composition and valence state of the prepared nano metal oxide catalyst Ni3V2O8-30h, XPS test was carried out. Figure 3 The XPS spectra of Ni 2p, V 2p and O1s of Ni3V2O8-30h in Example 1 show that V is V 5+ The Ni forms include Ni 2+ and satellite peaks, indicating the successful preparation of Ni3V2O8 catalyst.
[0050] The performance of the Ni3V2O8 doped aluminum hydride composite hydrogen supply material prepared in this example was measured. Figure 4 As shown, the initial dehydrogenation temperature is reduced to 72-75°C, and the dehydrogenation amount reaches 8.2wt%; at 100°C, the dehydrogenation amount in 20 minutes is 6.3wt%, which has excellent dehydrogenation performance.
[0051] Example 2-4 Preparation method of nano-metal oxide Ni3V2O8 doped with aluminum hydride composite hydrogen supply material
[0052] In this Example 2-4, nano metal oxide catalyst Ni3V2O8 doped aluminum hydride composite hydrogen supply material is prepared. The specific process is similar to that of Example 1, and the only difference is that the technical parameters in the preparation process are different.
[0053]
[0054] Comparative Example
[0055] In order to explore the effects of different parameters during the preparation of composite materials on their properties, the following groups conducted different experiments, as follows.
[0056] Group A: Preparation of AlH3-5wt% V2AlC composite hydrogen storage material. The preparation process is similar to that of Example 1, except that: step S2 does not occur, and the V2AlC prepared by S1 is directly used as a catalyst. The V2AlC and aluminum hydride composite hydrogen storage material is prepared according to the process and proportion of S3, and is recorded as AlH3-5wt% V2AlC.
[0057] Group B: AlH3 hydrogen storage material without adding any catalyst, recorded as AlH3-As-received.
[0058] Group C: AlH3-5wt% Ni3V2O8 composite material was prepared. The preparation process was similar to that of Example 1, except that the V2AlC powder prepared in step S1 was purchased from the market.
[0059] Group D: AlH3-5wt% Ni3V2O8 composite material was prepared. The preparation process was similar to that of Example 1, except that: in step S1, the mass ratio of nickel nitrate hexahydrate to V2AlC powder was 62:5.
[0060] Group E: AlH3-5wt% Ni3V2O8 composite material was prepared. The preparation process was similar to that of Example 1, except that the molar ratio of raw materials used in preparing V2AlC powder in step S1 was: V:Al:graphite powder = 2:1.2:1, and the size of V2AlC powder used in step S2 was: 300 mesh
[0061] Group F: Preparation of MgH2-5wt% Ni3V2O8 composite material. The preparation process is similar to that of Example 1, except that the hydrogen storage material in step S3 is replaced by MgH2.
[0062] The hydrogen release performance of the materials prepared by Group A and Group B was measured. The specific results are shown in Figure 4 As shown in the figure, it can be seen that the starting and ending dehydrogenation temperatures of the AlH3-As-received sample are 125 and 157°C, respectively, and the dehydrogenation amount is 9.2wt%; after adding 5wt% V2AlC, the starting and ending dehydrogenation temperatures are reduced to 92°C and 150°C, respectively, and the dehydrogenation amount is reduced to 8.3wt%. Compared with the AlH3-As-received sample and the AlH3-5wt% V2AlC sample, the AlH3-5wt% Ni3V2O8 composite material has a more suitable dehydrogenation temperature.
[0063] The performance of materials in groups C to F was measured, as shown in the table below.
[0064]
[0065] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a nano-metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material, characterized in that: Follow the steps below in order: S1. Preparation of precursor V2AlC V powder, Al powder and graphite powder were uniformly mixed in a molar ratio of 2:1.3:1, and V2AlC powder was prepared by a solid phase sintering method; S2. Preparation of Nano-Metal Oxide Catalyst Ni3V2O8 Nickel nitrate hexahydrate was dissolved in 10% acetic acid solution, and then V2AlC powder was added, and after ultrasonic dispersion, it was transferred to a hydrothermal reactor and subjected to a solvent thermal reaction in a 200°C forced air drying oven for 12 to 36 hours. The product after the reaction was centrifugally washed and dried, and the product was collected to obtain a nano-metal oxide catalyst Ni3V2O8; S3. Preparation of nano-metal oxide catalyst Ni3V2O8 doped aluminum hydride composite hydrogen supply material Aluminum hydride and nano-metal oxide catalyst Ni3V2O8 were mixed and a composite hydrogen supply material was prepared by mechanical ball milling in an argon atmosphere.
2. The method for preparing a nano-metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material according to claim 1, characterized in that: In step S1, the molar ratio of V powder, Al powder and graphite powder is 2:1.3:1, and the solid phase sintering method uses argon as the sintering atmosphere. The temperature is first increased to 600°C at a heating rate of 5°C / min, and then increased to 1500°C at a heating rate of 10°C / min. The reaction temperature is 1500°C and the reaction time is 300min.
3. The method for preparing a nano-metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material according to claim 1, characterized in that: In step S2, the mass ratio of nickel nitrate hexahydrate to V2AlC powder is 93:15, and the size of V2AlC is 600 mesh.
4. The method for preparing a nano-metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material according to claim 1, characterized in that: In step S2, the centrifugal washing is performed using deionized water and anhydrous ethanol at a rotation speed of 8000 rpm and a single centrifugation time of 3 minutes, first centrifuging with deionized water for 4 to 6 times and then centrifuging with anhydrous ethanol for 2 to 3 times.
5. The method for preparing a nano-metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material according to claim 1, characterized in that: In step S2, the drying temperature is 60° C. and the drying time is 24 hours.
6. The method for preparing a nano-metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material according to claim 1, characterized in that: In step S3, the doping amount of the nano metal oxide catalyst Ni3V2O8 is 5wt%.
7. The method for preparing a nano-metal oxide Ni3V2O8 doped aluminum hydride composite hydrogen supply material according to claim 1, characterized in that: In step S3, the ball-to-material ratio of the mechanical ball milling is 60:1, the ball milling speed is 350 r / min, the ball milling time is 1 h, and the volume of the ball milling jar is 250 mL.
8. The method for preparing a composite hydrogen supply material of nano metal oxide Ni3V2O8 doped with aluminum hydride according to any one of claims 1 to 7, characterized in that: The nano metal oxide catalyst Ni3V2O8 is a cone-shaped structure similar to the shell of a durian.
Citation Information
Patent Citations
Composite hydrogen storage material for complexing hydrides and hydrogen storage alloys
CN101992056A
Aluminum hydride hydrogen storage material doped with transition metal fluoride and preparation method thereof
CN103771337A